Pengaruh Animosity, Ethnocentrism, Subjective Norm terhadap Fast Food Boycott Intention yang Terafiliasi dengan Israel - Nilnal Muna; Muhammad Sadat, Andi; Putri Kusumaningtyas, Daru (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Partial Least Squares Structural Equation Modeling (PLS-SEM) is a quantitative analysis technique used to measure the relationships between latent variables simultaneously. The purpose of this study is to examine the influence of animosity, ethnocentrism, and subjective norms on fast food boycott intentions in global brands such as McDonald's and KFC affiliated with Israel. Data was collected from 200 respondents spread across seven major cities on the island of Java, namely Jakarta, Bogor, Tangerang, Bekasi, Bandung, Surabaya, and Semarang. The measurement was carried out using 20 indicators from four variables with a Likert scale of 6. The model was analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through Smart PLS software version 4. Most respondents were young women and college students, which were the dominant group in this study. The results of the study showed that the three variables, namely animosity, ethnocentrism, and subjective norms, had a positive and significant effect on fast food boycott intention directly.